2017
DOI: 10.1016/j.solener.2017.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Optimal switchable load sizing and scheduling for standalone renewable energy systems

Abstract: The variability of solar energy in off-grid systems dictates the sizing of energy storage systems along with the sizing and scheduling of loads present in the off-grid system. Unfortunately, energy storage may be costly, while frequent switching of loads in the absence of an energy storage system causes wear and tear and should be avoided. Yet, the amount of solar energy utilized should be maximized and the problem of finding the optimal static load size of a finite number of discrete electric loads on the bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Thus, heuristic techniques can overcome the drawback of numerical algorithms. In addition to that, some of the studies combined two or more in order to enhance the converge to the optimal values and reduce the execution time, such as the research works presented in [43,47,48]. Hussein et al [46] proposed an optimal design of the SAPV system using multi-objective particle swarm optimization (MOPSO) in Malaysia.…”
Section: Optimization Methodsmentioning
confidence: 99%
“…Thus, heuristic techniques can overcome the drawback of numerical algorithms. In addition to that, some of the studies combined two or more in order to enhance the converge to the optimal values and reduce the execution time, such as the research works presented in [43,47,48]. Hussein et al [46] proposed an optimal design of the SAPV system using multi-objective particle swarm optimization (MOPSO) in Malaysia.…”
Section: Optimization Methodsmentioning
confidence: 99%
“…In this study, the decision variables were the total cost of photovoltaic panels, the angle of the surface of these panels, and the continuous and stable power generated by this HRE microgrid. Habib et al [26] also designed and simulated a renewable energybased microgrid. These researchers optimized factors such as the angle of inclination and latitude of the solar panel's surface, the maximum power point of the solar panels, and the lifespan and efficiency of the battery bank and inverters.…”
Section: Solar Energy Modelingmentioning
confidence: 99%
“…Kiehbadroudinezhad et al [5], in their research, concluded that the reliability, total annual cost, and gas emissions' volume of the HRES are the most important factors that should be considered for the modeling, optimization, and evaluation of wind and solar-based power generation microgrids. Habib et al [26] also found that the cost of the total power generation system increases in a renewable energy system if the size of the renewable resources is considered too large; if it is too small, then the system's reliability decreases. Gupta [39] introduced an optimization algorithm to optimize the size of an HRE microgrid based on wind and solar and used the requested load hourly data to model and optimize the HRE microgrid.…”
Section: Sizing Of the Solar-wind Energy Microgridmentioning
confidence: 99%
“…Some of software tools have been utilized for sizing of a SAPV system based on economic evaluation, and planning and analysis tools such as PV.sys, Transient System Simulation (TRNSYS), Hybrid Optimization Model for Electrical Renewable (Homer), improved Hybrid Optimization by Genetic Algorithm (iHOGA), RetScreen, and System Advisor Model (SAM) [25]. Several studies have employed hybrid methods by combining two methods or more to find an optimal design of the SAPV system [26][27][28][29]. The hybrid methods overcome the drawbacks of AI methods by high ability of convergence to optimal solutions and reducing the execution time.…”
Section: Introductionmentioning
confidence: 99%